Beach management tools - Concepts, methodologies and case studies - Azuz-Adeath, Isaac; Muñoz-Sevilla, Norma Patricia; Cortés-Ruíz, Alejandra (Springer, 2018)
Beaches respond in several time and space scales to physical phenomena like wind, waves, tides, storm-surges, littoral currents, river discharges and sea level rise. As a dynamical system they can also be changed due to the influence of biological, geological and chemical processes as well as human-related activities such as urban expansion and port development; construction of coastal protection infrastructure; resources extraction or production and, tourism related actions, among others. In order to properly manage the beaches, any proposed plan or program should preserve the natural structure and function of the beach. In this sense, coastal managers need to choose among several scenarios and managerial options based on the best scientific information available, and one of the most adequate method to do that considering the cost/benefit-, is looking at the results of coastal simulation models. This paper is focused on coastal processes and review some empirical and numerical models emanated from the coastal engineering arena that can be useful in the practice of coastal management; identify the stages of management in which should be used; and proposes strategies for the proper implementation, monitoring and review of the modeling results, in the context of local beach management.
From sediment movement to morphodynamic changes, Useful Information from the modeling world to the beach management practice
Keywords: Beach management; Beach changes; Sediment movement; Morphodynamic models; Sistemas